ПАРАДИГМАТИЧНІ ВІДНОШЕННЯ МІЖ ЛЕКСИКО-СЕМАНТИЧНИМИ ГРУПАМИ ПРИКМЕТНИКІВ У НАУКОВОМУ СТИЛІ АНГЛІЙСЬКОЇ МОВИ - Данилович, Оксана (Current issues of social studies and history of medіcine. Joint Ukrainian-Romanian scientific journal., 2021)
Oksana Danylovych. Paradigmatic relations between lexical-semantic groups of adjectives in the scientific style of the English language. The article is dedicated to the study of paradigmatic relations of adjectives on the semantic level in the scientific style. Paradigmatic ties in the nucleus and the first periphery are determined and compared. The object of study is adjectives in the scientific style. The subject of the study is paradigmatic ties on the semantic level. The goal is to investigate and compare paradigmatic ties of adjectives in the scientific style. The topicality is caused by the necessity of study of paradigmatic ties of adjectives in the scientific style as they have not been investigated yet. In our study the statistical method was used such as the correlation analysis which helps to determine intensity and character of ties. The more there is the dependence between signs, the more the quantity of coefficient of correlation will approach to 1. In case of the absence of the statistical dependence the quantity of coefficient of correlation will be about zero or equals zero. Using the quantity of usage LSG of adjectives were divided into the nucleus and the first periphery. Due to the correlation analysis paradigmatic ties of LSG of adjectives within the nucleus and within the first periphery and between them were found and analyzed. In our study the statistical method was used such as χ² - which shows presence or absence of a tie. The coefficient K indicates the force (intensity) of ties. Due to it the ties are divided into strong, mean and weak ones. Statistically meaningful ties of lexical-semantic groups (LSG) of adjectives were analyzed. A scientific novelty is in distinguishing the nucleus and the first periphery and investigating paradigmatic ties between them. Conclusions. LSG of adjectives within the first periphery create not a big number of ties in comparison with the number of ties with LSG of adjectives of the nucleus. LSG of adjectives “Natural and physical state” and “Space value of distance and duration” are distinguished as making up the biggest number of ties with nucleus. The study shows that LSG of adjectives within of the first periphery are more independent between themselves and are able to have free ties. Paradigmatic ties of LSG of adjectives within the nucleus have the tendency to dependence and a mutual influence.
PARADIGMATIC RELATIONS BETWEEN LEXICAL-SEMANTIC GROUPS OF ADJECTIVES IN THE SCIENTIFIC STYLE OF THE ENGLISH LANGUAGE
Keywords: combinability, adjective, lexical-semantic group, paradigmatic ties.